Analisis Beban Kerja Mental, Stres Kerja, Dan Tingkat Kelelahan Kerja Secara Ergonomis Pada Karyawan Bagian Operasional Pabrik Kelapa Sawit (PKS) PTPN V Sei Galuh Di Kabupaten Kampar - Bastian Simanungkalit, Adolf; Nauli Daulay, Iwan; Andreas Siregar, Prima (Program Studi Manajemen FEBM UMRAH, 2023)
The workload can be defined as the difference between the ability of employees to work with the demands of the work that must be carried out. The human workload is physical and mental. The workload can also influence the level of stress and level of fatigue received by employees. This study aims to determine the level of mental workload, work stress, and level of fatigue experienced by employees of the Palm Oil Mill Operational Section (PKS) PTPN V Sei Galuh in the District Kampar. The population in this study included all employees in the manufacturing, engineering, and quality control departments. The sampling technique using the census method, the sample of this study amounted to 117 people. The mental workload was measured using the NASA-TLX questionnaire, and work stress was measured with the Health and Safety Executive (HSE) questionnaire, while fatigue levels were measured using the Subjective Self Test Rating questionnaire from the Industrial Fatigue Research Committee (IFRC) Japan. The results of calculating the mental workload of employees in the category of moderate mental workload, with an average total score of 66.22. Employee work stress is in the category of moderate work stress with an average total score of 32.67. While the results of the IFRC questionnaire employees are in the category of moderate work fatigue with an average total score of 30.79.